Effectiveness of hormone therapy in patients with prostate cancer. Regional experience - P. G. Berezin; V. V. Milovanov; A. A. Ivannikov; N. A. Ognerubov (Исследования и практика в медицине)
Purpose of the study. To determine the effectiveness of antiandrogenic therapy — 10-year General and tumor-specific survival (OV, OSV) depending on the type of hormone therapy, the stage of the disease, and the risk of progression.Patients and methods. The study was based on a retrospective analysis of 100 patients with localized, locally advanced, and metastatic prostate cancer over the period 2008–2018. The assessment was conducted in 2019. All patients received antiandrogenic treatment in the form of castration therapy (n=59) and combined (complex) treatment (n=41) in various variants and modes for more than 5 years. Patients had a 100% 5-year survival rate. The control point of the study was General and tumor- specific survival, as well as prognostic factors that determine this survival. Results. By the end of the study, 53 (53%) patients were alive, 8 (8%) died, and 39 (39%) patients were censored. The highest percentage of 10-year overall survival was achieved in localized stages of the disease and was 52% (31 patients) — stage 1, 38% (22 patients) — stage 2. Tumor specific survival rate (1–2 stages) — 62% (33 patients). At stage 3–30% (14 patients) and 51% (21 patients) and at stage 4–18% (1 patient) and 32% (2 patients), respectively. Depending on the risk of progression (Gleason index), high rates of both General and tumor- specific survival were achieved with low Gleason (2–5), and moderate risk of Gleason progression (6–7), and were 85% and 62%, respectively. The most effective method of treatment that determines the 10-year overall survival was combined (hormone radiation) therapy, which allowed to achieve results in 75% of patients. The tumor — specific survival rate was more than 80%.Conclusion. In real clinical practice, the use of antideprivation therapy in various variants and modes allows to obtain a 10-year General and tumor- specific survival rate in 75% and more than 80% of patients. Stratification of patients by risk groups forms a personalized approach to the treatment of each patient. Use of research treatment regimens in the work STAMPEDE, CHAARTED allows to increase the overall survival of patients with metastatic stage of the disease.